Konut sigortalarının reel ve finansal sektör açısından değerlendirilmesi - Beyaz, Necat (My University, 2001)
GİRİŞ Türkiye gibi yüzölçümünün %66'sı aktif fay hattı üzerinde yer alan ve toplam nüfusunun %70'i bu aktif fay hattı üzerinde yaşayan bir ülkede özellikle 1999 yılında yaşanan Marmara ve Bolu Düzce depremlerinde 18.373 vatandaşımızın hayatını kaybetmesi, 15.165 işyerinin yıkılması ve ağır hasarlı hale gelmesi, 104.440 konut, 16.120 işyerinin orta derecede hasarlanması, 113.283 konut, 14.656 işyerinin ise hafif derecede hasarlanması kaliteli konut üretiminin ve sigortanın önemini bir kez daha ortaya koymuştur. Bunun dışında Devlet İstatistik Enstitüsü tarafından 2000 yılında yapılan bina sayımlarına göre; ülkemizde toplam 7.838.675 adet bina, ve 16.235.830 adet konut olduğu, binaların %48,4'ünün karkas, %51,1'inin yığma, ve deprem açısından son derece önemli olan tünel kalıp teknolojisi ile inşa edilen bina oranının ise %0.1 olduğu, ayrıca binaların %61.4'ünde tadilata ihtiyaç olmadığı %28.4'ünde basit tamir ve tadilata, %7.3'ünde esaslı tamir ve tadilata ihtiyaç olduğu, %1.7'sinin ise yıkılacak şekilde olduğu tespit edilmiştir. Yaşanan deprem felaketleri sonucunda oluşan bilanço ve Devlet İstatistik Enstitüsü tarafından yapılan bina sayımları ülkemizde konut üretiminin oldukça kalitesiz olduğunu ve konutların büyük çoğunluğunun sigortasız olması nedeniylede ülke ekonomisinin her deprem felaketinden sonra büyük bir darbe aldığını göstermektedir. Nitekim 1999 yılında meydana gelen deprem felaketleri sonucunda oluşan maddi hasarın 15 Milyar dolardan fazla olduğu belirtilmiştir. Bugün bu 15 milyar dolarlık rakam, ciddi bir ekonomik kriz içerisinde olan ülkemizin bu krizden kurtulması için IMF'den talep edilen kredi bedeli ile aynı değerdedir. İşte tüm bu sebeplerden dolayı deprem açısından çok ciddi riskler taşıyan ve ekonomisi bu depremleri kaldırmaktan çok uzak olan ülkemizde oluşacak maddi ve manevi hasarları azaltmaya yönelik olarak; konut üretiminin nitelik ve kalitesinin yükseltilmesi ve oluşacak her türlü riske karşı üretilecek konutların belirlenecek yeni bir zorunlu konut sigortası modeli ile sigorta altına alınması düşüncesinden hareketle böyle bir çalışma yapılması ihtiyacı hissedilmiştir. Konut Sigortalarının Reel ve Finansal Sektör Açısından Değerlendirilmesi adını verdiğimiz bu çalışmada, geliştirilecek yeni bir konut sigortası modelinin sigorta ve konut sektörünü nasıl etkileyeceği ve bu sektörlerde meydana gelecek genişlemelerin ülke ekonomisi içerisinde yer alan finansal ve reel sektör üzerindeki etkilerinin nasıl olacağı üzerinde durulmaya çalışılmıştır. Bu nedenle bu çalışmanın birinci bölümü olan Konut Sektörünün Ekonomik Analizi Bölümü'nde konut sektörü; konut talebi ve konut talebini belirleyen etmenler ile, konut arzı ve konut arzını belirleyen etmenler incelenerek konut sektörünün ülkemizdeki piyasa yapısını ve mevcut konut üretiminin konut talebini karşılayıp karşılamadığı tespit edilmeye çalışılmıştır. Bunun dışında yine bu bölüm içerisinde konut finansmanının nasıl gerçekleştirildiği ve konut finansman modelleri içerisinde merkezi yönetimin ne kadar etkili olduğu gibi konular üzerinde durulmaya çalışılmıştır. Son kısımda ise, konut sektörünün ülke ekonomisine olan etkileri ve bunun sonucunda da konut sektörü ile diğer sektörlerin birbirleriyle olan ilişkileri incelenmeye çalışılmıştır. II.Bölüm olan Sigorta Sektörünün Piyasa Yapısı Bölümünde; ilk önce Türkiye'de uygulanan sigorta türleri ve uygulanan bu sigortaların kapsamları çok detaylı bir şekilde incelenmeye çalışmıştır. Daha sonra ise sigorta sektörünün piyasa yapısı, kurumsal çerçevesi, prim portföyü, hasar gelişimi konular incelenerek sigorta sektörünün piyasa yapısı tespit edilmeye çalışılmıştır. Son kısımda ise, dünya sigorta sektörü incelenmeye çalışılmış ve sigorta sektörününün Türkiye'deki piyasa yapısı dünya ülkeleri ile karşılaştırılmaya çalışılmıştır. III Bölüm olan Konut Sektöründe Yürürlüğe Konulan Uygulamalar Bölümü'nde; Türkiye'de uygulanan yapı denetim modellerinin tarihsel süreci, 1999 yılında meydana gelen deprem felaketlerinden önce uygulanan yapı denetim modelleri ile; 1999 yılında meydana gelen deprem felaketlerinden sonra yürürlüğe konulan yapı denetim modelleri şeklinde incelenmeye çalışılmıştır. Yine bu bölüm içerisinde zorunlu deprem sigortası ve Dünya'da uygulanan yapı denetim modelleri incelenerek bu modellerin Türkiye'deki modelle karşılaştırılması yapılmaya çalışılmıştır. Bu çalışmanın son bölümü ve aynı zamanda çalışmamızın adını aldığı bölüm olan, Konut Sigortalarının Reel ve Finansal Sektör Açısından Değerlendirilmesi bölümünde, ilk önce konutlarla ilgili olarak uygulanmakta olan sigorta türleri üzerinde durulmaya çalışılmıştır. Uygulanan sigorta türlerinin konut sektörüne olan etkileri ve bu sigortaların yeterliliği ve kapsamları gibi konular üzerinde durularak konut sigortaları ile ilgili olarak farklı model arayışları içerisine girilmiştir. Daha sonra ise konutlarla ilgili olarak uygulanacak olan sigortaların ekonomiye dolaysı ile reel ve finansal sektör açısından değerlendirilmesi yapılmaya çalışılmış ve bu etkilerin sonuçları üzerinde durulmaya çalışılmıştır. Sonuç olarak bu çalışma ile başta deprem olmak üzere katastrofik risklerle karşı karşıya olan ülkemizde bu risklerden korunmak için konut üretiminin kalitesinin arttırılıp konut sektörünün genişlemesi ve ülke ekonomisinin sigorta sektöründen daha fazla pay alması için alınması gereken önlemler ve bu önlemlerin ekonomik sonuçları üzerinde durulmaya çalışılmıştır.

The Marmara and Bolu Düzce earthquakes of 1999, during which 18.373 people died; 15.165 business buildings were either totally destroyed or heavily damaged; 104.440 houses and 16.120 business buildings were partly-damaged; and 113.283 houses and 14.656 business buildings were slightly-damaged, have once more brought to the foreground the importance of house construction quality and insurance in a country like Turkey, 66% of the total area of which is on active fault lines and 70% of the population of which lives on these active fault lines. Furthermore, according to the results of the records collected by State Statistics Institute in 2000; it has been reported that there are a total of 7.838.675 buildings and 16.235.830 houses in our country, 48,4% of which are constructed in carcass style, and 51,1% are in stacked style. It has also been found that the number of buildings constructed by using the tunnelite casting technology, which is very important in relation to earthquake risk, is 0.1%, and that 61.4% of the total number of buildings do not require reconstruction, 28.4% require simple repair and reconstruction, 7.3% need substantial repair and reconstruction, and 1.7% of the buildings are to be deconstructed. The emerging balance sheet and the records of the total number of buildings prepared by State Statistics Institute show that house construction quality is very poor in our country and since the majority of these buildings are not protected by insurance, the economy of the country is significantly damaged after each earthquake disaster. Accordingly, it was reported that the financial loss after the earthquakes that occurred in 1999 was over 15 billion US dollars. Now, 15 billion dollars is equivalent to the amount of credit that is asked from the IMF in order to recover from the current serious economic crisis. Because of all the above mentioned reasons, and in keeping with the idea that in our country that faces serious earthquake risks and that is far from being able to come over the economic burdens of such disasters, for the purpose of keeping the material and spiritual damages at lower levels, the necessity of conducting a study which argues that the quality of house construction should be improved and the buildings should be protected against all kinds of risks by the introduction of a new and compulsory housing insurance model was felt. In this study, entitled the Evaluation of Housing Insurances in Relation to Real and Financial Sectors, the possible effects of developing a new housing insurance model on insurance and housing sector and the possible effects of the expansion of these sectors on the financial and real sectors in the country economy are dealt with. For this reason, in the first chapter of this study, that is Economic Analysis of the Housing Sector, the housing sector, housing demand and the factors that define the housing demand, housing supply and the factors that define the housing supply are studied for the purpose of finding out the market structure of the housing sector in our country, whether the present house construction meets the housing demand, how the financing of housing is actualised, the extent to which the central government is effective in housing finance models, the effects of the housing sector on the economy of the country, and consequently, the relationships among the housing sector and other sectors. In Chapter II, that is on the Market Structure of the Insurance Sector, firstly the types of insurance that are available in Turkey and the coverage of these insurance types are studied in detail. Then, a definition of the market structure of the insurance sector is attempted by means of studying the market structure of the insurance sector, its institutional frame, premium portfolio and damage development. In the last section, the insurance sector in the world is studied and the market structures of the insurance sectors in Turkey and other countries are compared and contrasted. In Chapter III, on Regulations Implemented in Housing Sector; the historical development of the construction regulation models that have been in effect in Turkey, the construction regulation models that have been in effect prior to the earthquake disasters of 1999, and the construction regulation models that have taken effect after the earthquake disasters of 1999 are studied separately. Within the same chapter, compulsory earthquake insurance and the construction regulation models used in the world are dealt with and these models are compared and contrasted with the model that is used in Turkey. In the last chapter, on the Evaluation of Housing Insurances in Relation to Real and Financial Sectors, after which the study is named, firstly, the insurance types that are used for housing are considered. Alternative models of housing insurance were tried to be defined by means of handling issues like the effects of the present insurance types on the housing sector, and the efficiency and scopes of these insurances. Then, the effects of housing insurances on economy and thus on real and financial sectors, and the consequences of these effects are discussed. The study concludes that the present housing sector in Turkey, in which there is more demand than supply, is potentially a key sector for the economy with its sophisticated market structure. With regard to the quality of the houses that are constructed, however, the present housing sector is in the position of a sector in which construction of houses that pose serious threats to human life are actualised. The reason for this is the presence of a system called build and sell, in which most of the houses are constructed by small-scale contractors and without an effective construction regulation and insurance. The most dangerous threat posed by the constructions built by small-scale contractors, who are in the build and sell system, stems from Turkey's location on the earthquake zone. As a result of the earthquakes of past few years, the houses constructed by these individuals have been vulnerable against vibrations, which would not technically give damage, and thus, these houses pose serious threats on human life. Apart from these, it is not possible to suggest the same evaluation for the large firms that are specialised in house construction. Consequently, despite the fact that it has the potential to contribute more to the economy, the lack of effective control and insurance systems for constructions and the resulting poor quality of construction makes the housing sector in Turkey one which poses important threats on human life. Hence, several measures concerning the housing sector should be taken urgently to improve these negative situations, to contribute to the economy and to safeguard human life. The location of a great section of our country on an earthquake zone and the abundance of unskilled labour force render this compulsory. Accordingly, with respect to the housing sector, the introduction of some regulations to ensure the construction of sanitary and qualified houses and the urgent implementation of these regulations will result in the better contribution of the housing sector to the economy of the country. With no doubt, one of the most important measures that should be taken is the implementation of a construction regulation model which will be supported by an effective and long term compulsory insurance. If we are to have a glance from the historical perspective at the construction regulation models that have been in effect in Turkey, prior to the earthquake disasters that occurred in 1999, construction regulation was implemented according to Public Works Law, Act number 3194. However, after the earthquake disasters, the poor quality of the constructions that were destroyed, and the damage given to almost all of the buildings located in the earthquake region, and the high number of deaths led to the overthrowing of the former system. Furthermore, according to an investigation conducted by State Planning Organization (DPT), when only the superstructure costs of the constructions are considered, the 1998 values of the buildings that have been destroyed during the earthquakes of the last 10 years, are equivalent to the 5.6% of tax incomes of 1998, to the 5.75% of the domestic debt stock, and to the 18.05% of the consolidated budget deficit of the same year. Therefore, the Decree by Law on Construction Control, Act number 595, which has been developed over the years and which includes novelties like the transfer of construction control authority from municipal administrations to independent establishments, took effect in the Official Gazette of 10 April 2001. The most important regulation, which was introduced by the Decree, was the compulsory financial responsibility insurance, but it has not been practised. The main impediment before the implementation of compulsory financial responsibility insurance was caused by the disagreement between construction control establishments and insurance companies concerning the amount of insurance. Yet, the newly-introduced construction control model did not prove to be an efficient system to provide qualified house construction. With the Decree by Law only the financial burden of the state was lessened, since it provided that in case of the destruction or damaging of buildings, because of earthquake or any other reason, all of the compensation was to be paid by construction control establishments. For this end, the new system foresaw that construction controls were to be carried out by construction control establishments and that these establishments would be responsible for any kind of risk to buildings during the 10-year-period following construction. However, despite all these regulations, Decree by Law on Construction Control, Act number 595 was annulled on 24 May 2001 upon the appeal of opposition parties to the Constitutional Court. After the cancellation of the Decree, construction control was temporarily conducted according to Public Works Law, Act number 3194, and on 29 June 2001 Construction Control Act number 4708 took effect. However, the total lack of an insurance concept that is required especially for an effective construction control model and high quality construction in this model shows that Construction Control Act number 4708 cannot be influential in ensuring qualified house construction. For this reason, in order to provide sanitary and safe house construction, an insurance model that is different from the present housing insurances should be implemented urgently. The regulation that should be introduced for housing insurance should also be long term and compulsory as in the insurance models in developed countries. The introduction of such an insurance model will both reinforce construction quality and contribute significantly to the development of the insurance sector, which has a 0.1% share in national income. Since the insurance sector depends on premium collection, the development and expansion of the insurance sector and its contribution to the economy will only be possible with the increase of premium production. When the contribution of the insurance sector in Turkey to the economy is compared with Western countries, it is seen that in Western countries insurance sector is a key sector that contributes to their economy, whereas in Turkey this is not the case. According to the Sigma data for 1999, Turkey is 39th in world premium production, and is placed in the 57th position in terms of premium production per capita. The branch that has the largest share in Turkey's total premium production, according to data for 2000, is casualty insurance by 49% of the share. Casualty branch is followed by life insurance with 18% and by fire insurance branch with 14% of the total. The proportion of the insurances concerning housing within machinery installation and fire insurances in all the branches was, according to data for 2000, 5.6%. This reveals that in the housing sector, which has the potential to become a leading sector in Turkish economy due to the presence of more demand than supply, there is a large uninsured capacity. Because of all these reasons, the regulations that will be introduced in Turkey for housing insurances will both reinforce the safe and high quality construction of houses in our country, which is situated on an earthquake zone, and contribute significantly to the development of the insurance sector. It is at this point that the effects of housing insurances on real and financial sectors are revealed. The real and financial effects of housing insurances will be in the form of the development and expansion of housing and insurance sectors and other sectors that are related to these sectors. The reason is that the implementation of a long-term compulsory insurance model with a wide coverage will play an important role in the construction of qualified houses and thus lead to the development of the housing sector. Consequently, all the sectors related to the housing sector such as iron and steel industries, aluminium industry, ceramic industry, plaster and concrete industries, paint industry and brick industry will develop and expand. Since the financial effects of housing insurances will be in the form of development and expansion especially of the insurance sector, this will lead to the further contribution of the insurance sector, which is underdeveloped in our country, to the economy. Since insurance sector depends on premium collection, an insurance model that will be introduced will also reinforce the capacity of insurance companies, by means of increasing total premium production, in creating more funds and using these funds in investments. As a result of this, insurance sector will perhaps become the leading sector in economic development.
Keywords: Konut-Türkiye; Sigortacılık